Особливості роботи і використання мікропроцесорів - Висоцький, А. В.; Штих, І. А. (ХНУРЕ, 2018)
With the development of technology and circuitry IC has emerged the creation of a single electronic device, such as a radio receiver, meter or control unit, on one crystal. But the construction of control devices based on universal ICs The average degree of integration, although it is less, is also not a good way to go, because the changes in the algorithm thus lead to a change in the electrical circuit of the control device (completely or in some parts of it).
Keywords: мікропроцесор; мікропроцесорна система